EXAMINATION OF HIGHER EDUCATION ADMINISTRATORS’ INFORMATICS LEADERSHIP - Batur, Özgür; Cantaş, Çiğdem; Mahmutoğlu, Cemaliye (International Online Journal of Education and Teaching, 2024)
This research was conducted to examine academicians’ perceptions of informatics leadership in three private universities located in the Turkish Republic of Northern Cyprus (TRNC) by using the Informatics Leadership Scale developed by Ulutaş & Arslan (2018). The study aimed to investigate whether factors such as participants’ gender, affiliated university, academic title, administrative experience, and field of education had an impact on the perceptions of administrators’ informatics leadership. Findings reveal that none of these factors had a significant impact. However, there was a significant difference in the Information sub-dimension of the scale between academicians with 1-5 years of teaching experience and those with 6-10 years of teaching experience. Likewise, there was a significant difference in the Information sub-dimension of the scale between participants with administrative duties as Dean and Vice-Dean compared to those with no administrative duties. Overall, it was found that the participants’ perception of informatics leadership was at a mid-level in all sub-dimensions and for the scale’s total score. This possibly mean that there is a need for improvement in the quality of informatics leadership provided by the participants. The findings of this study may be useful for administrators and policymakers in improving the quality of informatics leadership in higher education institutions.